2010
DOI: 10.1111/j.1468-2494.2009.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the scalp with ‘dry’ wash shampooing (DW) on Chinese men: an in vivo study

Abstract: Cosmetic habits show a strong diversity worldwide. The same applies to procedures that are considered as basic hygiene acts such as shampooing. Apart from common traditional shampoo routine, a special shampoo procedure, 'dry' wash is daily performed in Chinese hair salons. Without pre-wetting step, hairdresser applies the shampoo directly to dry hair with small quantity of water to create foam. Hand massaging is then offered on the scalp. This shampooing process is distinguished from traditional 'regular wash'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The barrier is no longer as effective as normal skin at reducing moisture vapor transmission (35) nor is it as effective at reducing the penetration of exogenous materials, such as topical application of a solution containing histamine (36). This impaired barrier fiinction leads to acceleration of the condition progression, likely disposing the skin to be less effective at blocking the penetration of the inflammatory initiators originating from Malassezia metabolic activity.…”
Section: The Impact On the Structure And Function Of Epidermismentioning
confidence: 93%
See 1 more Smart Citation
“…The barrier is no longer as effective as normal skin at reducing moisture vapor transmission (35) nor is it as effective at reducing the penetration of exogenous materials, such as topical application of a solution containing histamine (36). This impaired barrier fiinction leads to acceleration of the condition progression, likely disposing the skin to be less effective at blocking the penetration of the inflammatory initiators originating from Malassezia metabolic activity.…”
Section: The Impact On the Structure And Function Of Epidermismentioning
confidence: 93%
“…As expected, function follows structure and, as the structure improves due to treatment, so does the function of the skin. Barrier structural integrity as assessed by comeosurfammetry improves (37) as does a normalization of TEWL (35).…”
Section: The Impact On the Structure And Function Of Epidermismentioning
confidence: 99%
“…O'Goshi performed TEWL and surface hydration measurements on scalp skin but on hairless scalp, on subjects with male pattern baldness and with alopecia, and Liu et al . observed higher TEWL through dandruff skin. Laden reported that dandruff flakes have a reduced water‐holding capacity compared with skin samplings from the back of the hand but did not examine skin flakes from non‐dandruff scalp .…”
Section: Discussionmentioning
confidence: 69%
“…Some studies on scalp skin barrier quality have begun to address this. It has been reported that dandruff scalp skin has higher transepidermal water loss (TEWL) than healthy scalp skin . Also, the level of skin lipids is reduced and ratios between lipid types differ in dandruff skin, and their structural organization is more disorganized .…”
Section: Introductionmentioning
confidence: 99%
“…[11] The samples were given by the Pharmaceutical Science and Research Centre "Aliyance Krasoty" (Beauty Alliance, Kyiv, Ukraine). Lactic acid (Lactic Acid, "Galactic," Belgium) was used as a pH adjuster of the foaming base value.…”
Section: Methodsmentioning
confidence: 99%